Design of p‐WSe2/n‐Ge Heterojunctions for High‐Speed Broadband Photodetectors. (7th October 2021) - Lee, Chan Ho; Park, Youngseo; Youn, Sukhyeong; Yeom, Min Jae; Kum, Hyun S.; Chang, Jiwon; Heo, Junseok; Yoo, Geonwook
Abstract: Van der Waals (vdW) 2D/3D heterostructures are extensively studied for high‐performance photodetector applications. Until now, the type of 2D materials has been the primary area of interest rather than the design of 3D semiconductors. In this study, high‐speed broadband photodiodes (PDs) based on vdW p‐WSe2 /n‐Ge heterojunctions are reported, and the performance compared with different n‐Ge regions formed via the ion‐implantation process. The fabricated PD with a typical long n‐Ge region and low doping concentration responds to a broad spectral range from visible to infrared near 1550 nm with a response time of ≈3 µs and responsivity of 1.3 A W −1 . The inferior responsivity of PDs with short n‐Ge regions can be improved as demonstrated by experimental results and process simulation. Density functional theory calculations are performed to estimate the variation of the energy band structures with the doping concentration of n‐Ge. Fast photoresponse and efficient carrier separation across the heterojunction can be expected regardless of the n‐Ge doping concentration. Based on the experimental results together with theoretical band structure and process simulation, it is shown that the heterojunction with an optimized n‐Ge design is a promising high‐speed broadband photodetector that can be implemented with complementary metal‐oxide‐semiconductor design and fabrication processes. Abstract : A high‐speed broadband photodetector based on vdW p‐WSe2 /n‐Ge heterojunction is demonstrated, and the performance is compared in the design aspect of Ge semiconductors. The results not only show that the p‐WSe2 /n‐Ge heterojunction can be a promising high‐speed broadband photodetector up to near‐infrared implementable in complementary metal‐oxide‐semiconductor design and process but also offers design strategies for photodetectors based on 2D/3D heterojunctions.